Investigation of coping skills of faculty of sport sciences students with sportive problems - Aycen Aybek (Ozlem Book Center, 2023)
The aim of this study is to examine the coping skills of students who are actively engaged in sports in the faculty of sport sciences in terms of various variables. The population of the study consists of students who study in the faculties of sport sciences in the Black Sea region and who are actively engaged in sports. The sample consists of students living in Samsun and Trabzon provinces and studying in faculties of sport sciences and doing active sports in the 2022-2023 academic year. The data of the study were collected using online questionnaire forms prepared by the researchers with the help of Google Forms. Personal information form and Inventory of Coping Skills for Sportive Problems were used as data collection tools of the study. SPSS 28.0 programme was used for data analysis. Findings: There is a significant difference (p<0.05) in the sub-dimensions of high performance under pressure, being free from anxiety, confidence and success motivation in the comparison of the participants' grades and coping skills with sportive problems. In the comparison of the age of the participants and their coping skills with sportive problems, there is a significant difference in being away from anxiety, confidence and achievement motive (p<0.05). There was a significant difference in the sub-dimensions of being away from anxiety, confidence and achievement motive in the comparison of the coping skills with sportive problems according to the age of the students of the faculty of sport sciences and the sub-dimensions of the coping skills with sportive problems scale (p<0.05). It is recommended that more studies should be carried out in order for athletes to cope with sportive problems.